PS8:162 Disease pattern of male lupus. (21st March 2018) - Klyukvina, N; Nasonov, E
Abstract : Introduction: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease that occurs primarily in women (9:1 compared to men). Available data argue that gender and sex hormones modify susceptibility to, and expression of SLE. Subjects and methods: One hundred and fifty male patients (pts) aged 15 to 64 years (mean age 30, 5 y) with a valid diagnosis of SLE who had been followed up for 15 years were assessed. Results: The mean age at onset was 20 year (range 6–62 years). The distribution of disease onset by decade of age was following: between the ages of 6–20 y – 80 pts (53%), 21–40 y – 49 pts (33%), 41–64 y – 21 pts (14%). Mean duration from the onset to time of diagnosis valid SLE was 12 month (range 1–336). 77 pts were diagnosed during first year from disease onset. 35 pts had delay of true diagnosis for 5 and more years. The most common manifestations for men at disease onset were arthritis (50%), renal disease (16, 7%) and haematological abnormalities (23, 3%). During follow-up we observed malar rash (58%), arthritis (73, 3%), renal disease (54, 7%), CNS involvement (49, 4%), photosensitivity (51, 3%), discoid lupus (14%), mucosal ulcers (28%), serositis (32, 7%), haematological (72%) and immunological (93, 3%) abnormalities. 41 male pts (27, 3%) satisfied classification Sapporo criteria of definite antiphospholipid syndrome (APS)/Vascular thrombosis developed in 41 pts: 26 pts had only venous thrombosis, 8 pts – merely arterial thrombosis, 7 pts – a+v thrombosis. Pts with APS had higher frequency of livedo reticularis (13 pts, 31, 7%), pulmonary hypertension (8 pts, 19, 5%) and heart valve disease (20 pts, 48, 8%) in comparison to pts without APS (11, 9%, 6, 5%, 16, 6% respectively). Conclusion: The present investigation do not confirm older age at disease onset among men with SLE: one half of our pts were younger 20 y at disease onset. We found high frequency of arthritis, renal disease and neuropsychiatric manifestations over the course of illness. CNS involvement was the rare initial symptom. Men with SLE often had delay of valid diagnosis of SLE. We observed high incidence of definite APS in men with SLE.